Identifying Stakeholder Values for an eHealth Intervention to Facilitate Home-Based Geriatric Rehabilitation: A Qualitative Multi-Method Approach - Michael Bernardus Gustaaf Zonneveld MSc; Margriet Christine Pol PhD; Wilco Pieter Achterberg MD, PhD; Eléonore Françoise van Dam van Isselt PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2025)
Despite the existing need for an integrated eHealth intervention for home-based geriatric rehabilitation, it has never, to our knowledge, been developed through co-creation with the stakeholders. This study aims to identify values (based on stakeholders’ needs and preferences) regarding an eHealth intervention that fits the context of home-based geriatric rehabilitation. The multi-method qualitative design of this study comprised multiple qualitative methods (focus groups, interviews, and brainstorming sessions) and a survey. An agile science approach allowed for iterative data collection and analysis until an optimal fit was achieved. Recommendations from The Center of eHealth Research and Disease Management (CeHRes) Roadmap were used. Fourteen key stakeholders were identified, seven of which were represented in a project team that co-created the steps of this research. Based on the results of the qualitative methods, 15 eHealth attributes were formulated that captured the needs or preferences of the stakeholders. These resulted in the formulation of seven stakeholder values: (1) Fit with the patient’s digital skills and needs, (2) Blended care, (3) Personalized, (4) Safety at home, (5) Affordability, (6) Support, and (7) Privacy. Co-creation with stakeholders is necessary for the development of eHealth interventions in home-based geriatric rehabilitation. The most prominent key stakeholder is the patient. eHealth should match with the digital skills of the patient and preferably be delivered as blended care. The formulated values should be incorporated in future development of eHealth interventions.